Successful Renal Transplantation after Presumed Cyanide Toxicity Treated with Hydroxocobalamin and Review of the Literature - Ryan J. Hendrix; Paulo N. Martins; Jeffrey S. Stoff; Aaron Ahearn; Adel Bozorgzadeh; Babak Movahedi (Case Reports in Transplantation)
We report two cases of successful renal transplantation with allografts from donors who suffered anoxic brain injury as the primary cause of death from house fires. Each was treated prophylactically with hydroxocobalamin (Cyanokit) for suspected cyanide toxicity. During organ procurement, gross examination was notable for deep discoloration of the parenchymal tissues. Approximately 6 and 18 months after transplantation, both recipients have excellent renal graft function and remain independent from hemodialysis (HD). Hydroxocobalamin is the antidote for suspected acute cyanide toxicity. While largely tolerated by the recipient, there is concern over the potential functional implications of the associated side effects of dramatic tissue discoloration and development of oxalate crystals. Furthermore, difficulties performing hemodialysis in patients treated with hydroxocobalamin have been reported due to discoloration of the effluent fluid impacting the colorimetric sensor, causing false alarms and repetitive interruptions. As such, many transplant centers in the United States (US) continue to reject these organs. We seek to highlight two cases of successful transplantation following donor administration of hydroxocobalamin (Cyanokit) and present the first documented case of successful perioperative intermittent hemodialysis following transplantation of an allograft exposed to hydroxocobalamin. Furthermore, we emphasize the importance of optimal organ utilization and caution against unnecessary refusal.